Linezolid resistance in clinical isolates of Staphylococcus epidermidis from German hospitals and characterization of two cfr-carrying plasmids. (3rd March 2015) - Bender, Jennifer; Strommenger, Birgit; Steglich, Matthias; Zimmermann, Ortrud; Fenner, Ines; Lensing, Carmen; Dagwadordsch, Urantschimeg; Kekulé, Alexander S.; Werner, Guido; Layer, Franziska
Abstract: Objectives: This study was a detailed investigation of Staphylococcus epidermidis clinical isolates exhibiting linezolid resistance. Methods: Thirty-six linezolid-resistant S. epidermidis from eight German hospitals, including isolates from suspected hospital-associated outbreaks between January 2012 and April 2013, were analysed with respect to their antimicrobial susceptibility and the presence of cfr and/or mutations in the 23S rRNA, rplC, rplD and rplV genes. Relatedness of isolates was estimated by MLST and SmaI macrorestriction analysis. Characterization of cfr plasmids was carried out by means of Illumina sequencing. Results: The MICs of linezolid varied substantially between the isolates. No apparent correlation was detected between the level of resistance, the presence of cfr and ribosomal target site mutations. S. epidermidis isolates from two hospitals were confirmed as clonally related, indicating the spread of the respective clone over a period of 1 year. Next-generation sequencing revealed two different categories of cfr -expressing plasmids, both of them varying in genetic arrangement and composition from previously published cfr plasmids: p12-00322-like plasmids showed incorporation of cfr into a pGO1-like backbone and displayed capabilities for intra- and inter-species conjugational transfer. Conclusions: To date, linezolid-resistant S. epidermidis have rarely been isolated from human clinical sources in Germany. Here, we describe the emergence and outbreaks of these strains. We detected previously described and novel point mutations in the 23S ribosomal genes. The cfr gene was only present in six isolates. However, this is the first known description of cfr incorporation into conjugative vectors; under selective pressure, these vectors could give reasonable cause for concern.